(untitled) (International Journal of Geoscience, Engineering and Technology, 2023)
Urbanization progress has a direct impact on urban drainage due to the increase in impermeable surfaces. Ignoring these factors during urban planning can result in negative environmental consequences and a reduced quality of life in urban areas. Geoprocessing tools, such as GIS, are valuable for visualizing and characterizing study areas, facilitating data collection for terrain studies. This study focuses on characterizing the surfaces of three districts in Teófilo Otoni, MG: Castro Pires, Jardim São Paulo, and Santa Clara. These districts are distributed across two regions with different urban occupation patterns. We applied the Rational, Modified Rational, and Curve Number methods to estimate surface runoff and analyze variations over a 20-year period. Additionally, we utilized the USLE Method to estimate erosion. Data collection was conducted using ArcMap and Google Earth software. We observed a medium increase of 126% in the impermeable area across the three districts over the 20-year period. Surface runoff depth increased by 36% when using the rational methods and by 57% when applying the curve number method. Furthermore, we identified that the Rational Method tends to overestimate surface runoff depth. Conversely, soil erosion decreased in all three districts: 12.8% in Santa Clara, 18.0% in Castro Pires, and 20.4% in Jardim São Paulo. Our results illustrate the substantial influence of land use and urban development on erosion processes, particularly as a result of the expansion of impermeable surfaces in the studied areas.